PENGARUH DIGITALISASI DAN DATA CENTRE TERHADAP KINERJA KARYAWAN PT.XYZ - Purwatiningsih Purwatiningsih (Universitas Pamulang, 2022)
PT. XYZ, which is tasked with assisting companies in carrying out information activities, including specific information systems, general information, multimedia and opinion counters within the company, has a very important role in publicizing and disseminating various company activities and leadership policies throughout Indonesia. With limited employees who are superior, qualified, professional and competent in providing better public services, it is necessary to increase the quality and quantity of employees in carrying out their duties. One of the factors that influence the performance of PT. XYZ in this study is digitization. The purpose of digitization is to make it easier for employees to convey, provide, compile and explain information received by PT. XYZ to be processed and used as information suitable for consumption by the public. In carrying out its work, information systems require good data center support. This data center is big data for all levels of Company information, where all information can be accessed through the data center. The purpose of this study was to examine the effect of digitization and data center on the performance of PT. XYZ employees. The sample used in this study were PT. XYZ employees totaling 99 respondents. The sampling technique used is non-probability sampling, where not every respondent has the same opportunity to be sampled. The results in this study based on SPSS processing obtained the calculated t value for the digitization variable of 3.395 and the data center was 7.238, while the t table obtained was 1.661. This means that if t count > t table and the significance value is <0.05. So that it can be interpreted that there is an influence between digitalization and data center partially on performance. Based on the results of the f test, the calculated f value for the digitization and data center variables simultaneously is 54.697 while the f table obtained from the f table search is 3.091. So the results state that there is an influence between digitalization and the data center simultaneously on the performance of PT. XYZ employees. While the value of r2 = 0.533 which means that 53.3% of the performance variables can be explained by digitalization and the data center while the remaining 46.7% is influenced by other variables outside the model studied.Keywords: Digitization, Data Center, Performance, Employees, Management